2009
DOI: 10.1364/oe.17.000991
|View full text |Cite
|
Sign up to set email alerts
|

Flexible compact microdisk lasers on a polydimethylsiloxane (PDMS) substrate

Abstract: Compact microdisk cavities were fabricated on a polydimethylsiloxane substrate. The lasing of the flexible compact cavity was achieved with a low threshold power. The whispering-gallery mode of the microdisk was also characterized with three-dimensional finite-difference time-domain simulation. The curvature dependence in output power and threshold was also demonstrated by bending the microdisk cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thanks to the development of electrochemical etching [21] and photoelectrochemical etching [22], ultra-thin GaN film has been demonstrated using chemical exfoliation in previous works [23][24][25], which makes gallium nitride microtube lasers possible. Previous studies of WGM lasers employed microdisks or microfiber embedded in a flexible substrate [26][27][28][29][30] as strain sensors. For example, a GaN microdisk laser with a diameter of 1.2 µm embedded in a polydimethylsiloxane (PDMS) substrate as a strain sensor has a blue-shift per stretching unit of about 4.0 nm [29].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the development of electrochemical etching [21] and photoelectrochemical etching [22], ultra-thin GaN film has been demonstrated using chemical exfoliation in previous works [23][24][25], which makes gallium nitride microtube lasers possible. Previous studies of WGM lasers employed microdisks or microfiber embedded in a flexible substrate [26][27][28][29][30] as strain sensors. For example, a GaN microdisk laser with a diameter of 1.2 µm embedded in a polydimethylsiloxane (PDMS) substrate as a strain sensor has a blue-shift per stretching unit of about 4.0 nm [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, polymer or organic photonic devices are commonly used because of their flexible applications and low cost. Recent studies have reported on III-V materials-based light emitting diodes [22], [23] and compact lasers [24]- [26] on flexible and stretchable polymer/organic substrates. Because the optical properties of compact lasers are sensitive to its geometry, this organic or polymer-semiconductor hybrid platform allows fine-tuning of optical properties for small devices.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Besides the emission at the near-infrared or midinfrared regimes, the light sources with type-II QDs might also have advantages in photon stability, thermal stability, and an extra parameter to fine tune wavelength. 8 These advantages will benefit many applications such as optical integrated circuits, flexible optoelectronics, 14 or bioimage. 15 In this study, we demonstrated a compact microdisk cavity laser 16 made of type-II GaSb/GaAs QDs on GaAs substrate.…”
mentioning
confidence: 99%